Adaptation of pineal expressed teleost exo-rod opsin to non-image forming Photoreception through enhanced Meta II decay - Tarttelin, E; Fransen, M; Edwards, P; Hankins, M; Schertler, G; Vogel, R; Lucas, R; Bellingham, J (2011)
Photoreception by vertebrates enables both image-forming vision and non-image-forming responses such as circadian photoentrainment. Over the recent years, distinct non-rod non-cone photopigments have been found to support circadian photoreception in diverse species. By allowing specialization to this sensory task a selective advantage is implied, but the nature of that specialization remains elusive. We have used the presence of distinct rod opsin genes specialized to either image-forming (retinal rod opsin) or non-image-forming (pineal exo-rod opsin) photoreception in ray-finned fish (Actinopterygii) to gain a unique insight into this problem. A comparison of biochemical features for these paralogous opsins in two model teleosts, Fugu pufferfish (Takifugu rubripes) and zebrafish (Danio rerio), reveals striking differences. While spectral sensitivity is largely unaltered by specialization to the pineal environment, in other aspects exo-rod opsins exhibit a behavior that is quite distinct from the cardinal features of the rod opsin family. While they display a similar thermal stability, they show a greater than tenfold reduction in the lifetime of the signaling active Meta II photoproduct. We show that these features reflect structural changes in retinal association domains of helices 3 and 5 but, interestingly, not at either of the two residues known to define these characteristics in cone opsins. Our findings suggest that the requirements of non-image-forming photoreception have lead exo-rod opsin to adopt a characteristic that seemingly favors efficient bleach recovery but not at the expense of absolute sensitivity. © The Author(s) 2011. This article is published with open access at Springerlink.com.